Predicting microstructure and strength of maraging steels: Elemental optimisation. (15th September 2016) - Galindo-Nava, E.I.; Rainforth, W.M.; Rivera-Díaz-del-Castillo, P.E.J.
Abstract: A physics–based modelling framework to describe microstructure and mechanical properties in maraging steels is presented. It is based on prescribing the hierarchical structure of the martensitic matrix, including dislocation density, and lath and high–angle grain boundary spacing. The evolution of lath–shaped reverted austenite is described using grain–boundary diffusion laws within a lath unit. The dislocation density provides the preferential nucleation sites for precipitation, whereas descriptions for particle nucleation, growth and coarsening evolution are identified for Ni3 Ti, NiAl and its variants, and BCC–Cu clusters. These results are combined to describe the hardness at different ageing temperatures in several FeNi–, FeMn– and FeNiMn–based steels. A critical assessment on individual contributions of typical alloying elements is performed. Ni and Mn control the kinetics of austenite formation, where the latter shows stronger influence on the growth kinetics. Ti additions induce higher hardness by precipitating stronger Ni3 Ti, whereas Cu clusters induce low strength. A relationship between the reverted austenite and the total elongation in overaging conditions is also found. This result allows to identify optimal process and alloy design scenarios to improve the ductility whilst preserving high hardness in commercial maraging steels. Graphical abstract: